The effect of different dynamic stretch velocities on jump performance - Fletcher, I. M. (European Journal of Applied Physiology, 2010)
Dynamic stretching has gained popularity, due to a number of studies showing an increase in high intensity performance compared to static stretch modalities. Twenty-four males (age mean 21 ± 0.3 years) performed a standardised 10 min jogging warm-up followed by either; no stretching (NS), slow dynamic stretching at 50 b/min (SDS) or fast dynamic stretching at 100 b/min (FDS). Post-warm-up, squat, countermovement and depth jumps were performed. Heart rate, tympanic temperature, electromyography (EMG) and kinematic data (100 Hz) were collected during each jump. Results indicated that the FDS condition showed significantly greater jump height in all tests compared to the SDS and NS conditions. Further, the SDS trial resulted in significantly greater performance in the drop and squat jump compared to the NS condition. The reasons behind these performance changes are multi-faceted, but appear to be related to increases in heart rate and core temperature with slow dynamic stretches, while the greater increase in performance for the fast dynamic stretch intervention is linked to greater nervous system activation, shown by significant increases in EMG. In conclusion, a faster dynamic stretch component appears to prepare an athlete for a more optimum performance.